Effects of pancreas transplantation on oxidative stress in pulmonary tissue from alloxan-induced diabetic rats - Spadella, César Tadeu [UNESP]; Suarez, O. A. X. [UNESP]; Lucchesi, A. N. [UNESP]; Marques, S. F. G. [UNESP]; Cataneo, Antonio José Maria [UNESP] (Elsevier B.V., 2010)
Purpose. There is considerable evidence that cellular oxidative stress caused by hyperglycemia plays an important role in the genesis and evolution of chronic diabetic lesions. In this study, we determined the effectiveness of pancreas transplantation (PT) in preventing the imbalance caused by excessive production of reactive oxygen species over antioxidant defenses in lungs of rats rendered diabetic by alloxan injection.Methods. Sixty inbred male Lewis rats, weighing 250-280 g, were randomly assigned to 3 experimental groups: NC, 20 nondiabetic control rats; DC, 20 untreated diabetic control rats; and PT, 20 diabetic rats that received syngeneic PT from normal donor Lewis rats. Each group was further divided into 2 subgroups of 10 rats each which were killed after 4 and 12 weeks of follow-up. Plasma glucose, glycosylated hemoglobin, and insulin levels were determined in all rats. Lipid hydroperoxide (LPO) concentrations and enzyme activities of superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px) were measured in the pulmonary tissue of all rats.Results. The DC rats showed elevated blood glucose and glycosylated hemoglobin levels, with insulin blood levels significantly lower than the NC rats (P < .001). They also showed significantly increased LPO concentrations in the lungs (P < .01) after 4 and 12 weeks of follow-up. In contrast, SOD, CAT, and GSH-Px antioxidant activities were significantly reduced in these periods (P < .01) 12 weeks after diabetes induction. Successful PT corrected all clinical and metabolic changes in the diabetic rats, with sustained normoglycemia throughout the study. Excessive lung LPO production and low SOD, CAT, and GSH-Px antioxidant activities were already back to normal 4 weeks after PT.Conclusion. PT can control oxidative stress in pulmonary tissue of diabetic rats. It may be the basis for preventing chronic diabetic lesions in lungs.